Opinião pública democrática e soberania popular: por um paradigma republicano da liberdade de expressão - Ana Paola de Morais Amorim Valente (2013)
This thesis aims to discuss a concept of democratic public opinion taking as a departing point the paradigms of the republican thought, as a way to elaborate a language, distinct from the liberal one, which can offer an alternative to the organization of the question of the freedom of expression in the contemporary theories of democracy. In order to do so, we took as a reference the theoretical and methodological scheme developed in the historiographical practices dedicated to the study of the ideas, concepts, and political thought. We also incorporated the reference to the linguistic studies of Antonio Gramsci that guided the development of his concept of hegemony. The discussion followed two routes: the first brings the question of freedom o f expression to the debate between republicanism and liberalism regarding the concept of liberty , which is rather well developed in political philosophy. The second route aims to demonstrate that, in republican language, freedom of expression defense as an individual right depends on the reconstruction of a concept of democratic public opinion. In turn, democratic public opinion is defined as public space to defend a fundamental citizenship right, which enables the establishment of a bridge between individual liberty and public freedom, between the singularities of each citizen and the political body.